The Correlation Between Students’ Interest in Learning English and Their Learning Achievement - Musdalifah, Musdalifah; Fauzan, Muh. Miftah; Sally, Fauzan Hari Sudding (Journal of Excellence in English Language Education, 2025)
This study aims to find out what the students' interest is in learning English, to find out what the students' English learning achievement is, and to find out whether or not there is any correlation between the students' interest in learning English and their learning achievement. The method used was quantitative with a sample of 32 students of class VIII'6 using a random sampling technique. In obtaining data, researchers used questionnaires and documentation methods as research instruments. The results of data analysis show that students' interest in learning English and their English learning achievement fall into the high category, and the correlation between students' interest in learning English and their learning achievement has a positive correlation. The proof is with the F value of student learning interest and student learning achievement is 0.003 <0.05. Therefore, H0 is rejected and Ha is accepted. So, it is concluded that the correlation between students' interest in learning English and their learning achievement in English language learning in class VIII'6 SMPN 18 Makassar.